Cinematic Articulations of the Jungian ‘Symbolic’ and the Cultivation of Mindfulness in Hypno-Psychotherapy - Peters, Jan (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
Focussing primarily on Bergman’s Persona (1966) and Herzog’s Heart of Glass (1976), this essay examines how cinematic articulations of the Jungian Symbolic dovetail with hypnopsychotherapeutic modalities aimed at cultivating the ‘mindful’ awareness of the ‘groundlessness of being’. Mindfulness involves renouncing conceptions of who or what we are, so that we can dwell within an authentic ‘ground of being’ that is truly ‘groundless’. Likewise, Jung’s conception of the Symbolic refers to those numinous, unknowable aspects of the psyche that defy conceptualization. Heart of Glass documents the devastating consequences of a society that has sundered its vital connection to the Symbolic. In this connection, I suggest that the ability of trance states to set meanings adrift from their conventional moorings may provide the beleaguered villagers in Heart of Glass with the means by which they can restore the sundered link with this Symbolic realm. Persona, while ostensibly touching upon core Jungian concerns, exemplifies the pivotal theme in this essay, namely the assumption that Jung’s Symbolic resembles Lacan’s Register of the Real. Yet, the Lacanian Real is absolute plenitude, and thus is infinitely full and overdetermined. For life, movement and individuated consciousness to exist, a ‘space’, ‘void’, or ‘gap’ needs to be breached. I contend that Bergman’s cinematic articulation of the Jungian Symbolic effectively performs this task, and that hypnosis likewise seeks to create a clearing among the overgrown thickets of mental constructs that constitute a ‘false’ plenitude, or sense of self.